Environmental life cycle assessment of encapsulated rejuvenators from mining truck waste tires via pyrolysis for asphalt self-healing - Jose Norambuena-Contreras (Journal of Cleaner Production, 2025)
The application of pyrolysis to convert waste tires into fuels and engineering additives for asphalt self-healing is being actively explored by both industry stakeholders and researchers. This study presents, for the first time, a comprehensive evaluation of the technical and environmental implications of producing encapsulated liquid pyro-rejuvenators for asphalt self-healing applications. The analyses include experimental data on the production, characterization, and upgrading of crude pyro-oils, complemented by plant simulations and scale-up considerations. The pyro-rejuvenator produced after pyrolysis of mining trucks waste tires at 470 °C and distilled between 160 and 200 °C, contains BTX (14.6%), o-cymene (10.9%) and limonene (58%), and <10 cP viscosity, which confirms its feasibility for application in asphalt self-healing. Integrated mass balances results in yields of 27 wt% (pyro-rejuvenator), 11 wt% heavy fuel, 10 wt% light fuel and 5 wt% pyro-gas. The rejuvenator was encapsulated with 97% efficiency within thermochemically stable 1.5 mm alginate-based capsules produced by the vibrating jet method. Environmental Life Cycle Assessment results indicate that water consumption and electricity use during the encapsulation process heavily impact environmental performance, accounting for over 50%, necessitating the exploration of energy integration strategies. Finally, this study demonstrates the feasibility of producing a new generation of asphalt rejuvenators from waste tires sourced from mining trucks.